Accurate quantification of TAGs to identify adulteration of edible oils by ultra-high performance liquid chromatography-quadrupole-time of flight-tandem mass spectrometry. (March 2023) - Wei, Hailian; Yang, Dandan; Mao, Jin; Zhang, Qi; Cheng, Ling; Yang, Xianglong; Li, Peiwu
Graphical abstract: Highlights: A method for accurate quantification of TAGs by UHPLC-Q-TOF-MS/MS & CF3 is demonstrated. Optimum correction factor (CF3) involves response factors and relative molecular mass. This method shows higher accuracy, lower relative error and wider range than GC-FID. This method with principal component analysis can identify olive oil adulteration. Abstract: Edible oils play important roles in biological functions, and triacylglycerols (TAGs) in edible oils are complex mixtures. This makes accurate TAGs quantitation quite difficult that bring economically motivated food adulteration. Herein, we demonstrated a strategy for accurate quantification of TAGs in edible oils, which could be applied in identification of olive oil adulteration. The results showed that the proposed strategy could significantly improve the accuracy of TAG content determination, reduce the relative error of fatty acids (FAs) content determination, and present a wider accurate quantitative range than that of gas chromatography-flame ionization detection. Most important, this strategy coupled with principal component analysis could be used to identify adulteration of high-priced olive oil with cheaper soybean oils, rapeseed oils or camellia oils at a lower concentration of 2%. These findings indicated that the proposed strategy could be regarded as a potential method for edible oils quality and authenticity analysis.